Indoor environment modeling for interactive VR-based robot security service - Jo, Sangwoo; Kwon, Yong-Moo; Ko, Hanseok (ADVANCES IN ARTIFICIAL REALITY AND TELE-EXISTENCE, PROCEEDINGS, 2006)
This paper presents our simple and easy to use method to obtain a 3D textured model. Our algorithm consists of building a measurement-based 2D metric map which is acquired by laser range-finder, texture acquisition/stitching and texture-mapping to corresponding 3D model. The algorithm is applied to 2 cases which are corridor and space that has the four walls like room of building. The proposed algorithm can be applied to 2D/3D model-based remote surveillance system through WWW. The application terminals of this environment model for interactive VR that we consider are PC, PDA and Mobile phone. Especially, this paper introduces a case of service on WIPI-based mobile phone.